Rekonstruksi Citra Musik Hardcore Melalui Penciptaanvideo Musik Dengan Teknik Penyuntingan Compositing - Murtono, Taufik; Widakdo, Rio Koesuma (Seni Media Rekam ISI Surakarta, 2015)
The hardcore genre musician identical to muscular and tattooed body, violence, and they are familiar with alcohol or drugs. It blurs social messages are actually owned by many hardcore music. Through the concept of compositing editing techniques, in particular the incorporation of some elements of video, graphic design, and photography, editors emphasize the visual aspects of the slide motion graphics and special effects that direct imaging to reconstruct the audience to the perceptions of the creator or a singer. Two music videos of the band Spirit of Life, entitled Life Change for Me dan StopTalking Start Working, a musical genre that worked in the hardcore music video to be accepted by society. Music video works it is appropriate to visualize social development as informative and educative character. Through audio-visual artwork hardcore music can be seen as the music that gave social messages.Keywords : hardcore, video, music, compositing, genre, and reconstruction.